2018
DOI: 10.1080/09542299.2018.1507689
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of environmental risk from lead pollution of shooting range soils

Abstract: Risk assessment indices such as risk assessment code (RAC), potential ecological risk index (PERI), geoaccumulation index (I geo ), contamination factor (CF) and enrichment factor (EF) provide a good measure of environmental risk posed by Pb accumulated in shooting range soils as opposed to total Pb concentration. For this reason, the S/P Pistol shooting range, even though accumulated lower concentration of Pb (685±218 mg/kg), exhibited 'very high risk' to the environment with RAC value of 77 exceeding the 51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
12
0
4
Order By: Relevance
“…At two military shooting ranges in Korea, Eri value of Pb reached 3446, and 725, respectively [ 12 ]. In seven shooting ranges in Botswana, the Eri value of Pb ranged from 1192 to 56,272 [ 13 ]. Peddicord and LaKind [ 11 ] first evaluated the ecological risks of shooting rang contaminants for some animals, and found that Pb posed substantial risks to small mammals and grit-ingesting birds, but other contaminants, including As, Sb, Cu, Zn and PAHs posed minimal risks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At two military shooting ranges in Korea, Eri value of Pb reached 3446, and 725, respectively [ 12 ]. In seven shooting ranges in Botswana, the Eri value of Pb ranged from 1192 to 56,272 [ 13 ]. Peddicord and LaKind [ 11 ] first evaluated the ecological risks of shooting rang contaminants for some animals, and found that Pb posed substantial risks to small mammals and grit-ingesting birds, but other contaminants, including As, Sb, Cu, Zn and PAHs posed minimal risks.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, Pb in shooting range soils can be highly bioavailable, indicating a potential toxicity and environmental risk [ 3 ]. However, only few studies assessed their environmental and health risks [ 10 , 11 , 12 , 13 ]. Although several studies investigated heavy metal contamination status of shooting ranges in China, to our knowledge, no studies have been conducted on their ecological and health risks.…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by the presence of primary Pb carbonates which were the predominant products found in soils, indicating that soil organic matter does play a vital role in Pb bullet and shot weathering and also controls Pb migration within the soil [69]. Besides soil properties and leaching tests, other measures such as risk assessment indices can be applied to determine the mobility, bioavailability and bio-accessibility of Pb at shooting ranges to the ecosystem; these have been detailed by whose research showed that all of the seven shooting ranges studied presented 'high risk' to 'very high risk' to the ecological system [70].…”
Section: Mobility and Bioavailability Of Lead In Shooting Range Soilsmentioning
confidence: 99%
“…The iron sorbents immobilize Pb through its sorption by iron (III) hydroxides found in iron-based sorbents such as ferrihydrite, goethite and gibbsite [90]. Zerovalent iron (Fe°) will undergo weathering and corrode in the presence of oxygen and moisture leading to a variety of iron (hydr)oxides which provides new sorption and binding sites for Pb as shown in Equations (17)(18)(19) below [126].…”
Section: Iron-based Sorbentsmentioning
confidence: 99%
See 1 more Smart Citation